Misi Dalam Konteks Jemaat Antiokhia - Yahyo Yahyo (Publisher STPKat, 2022)
This article discusses mission studies in the context of the Antioch church. Mission problems that are increasingly evident in the practical realm need to be strengthened by analytical studies based on the biblical context as the foundation. By using a qualitative approach, descriptive method and supported by literature studies as a means of data collection. The result obtained is that the church needs to follow the example of the Antioch congregation in sending its congregation to mission and equipping them with relevant methods, systems and personalities.